2019
DOI: 10.1186/s40410-019-0106-z
|View full text |Cite
|
Sign up to set email alerts
|

Land use and urban sustainability assessment: a 3D-GIS application to a case study in Gozo

Abstract: Balancing urban growth and natural resource availability has been recognized as the main challenge of the 21st century from the strategic documents adopted by the recent World Summits. Agenda 21 advocates sustainable land use, as soil is a crucial natural resource to reduce urban vulnerability due e.g. to climate change, energy saving, and natural disasters. In this perspective, this paper aims at supporting local decision makers in identifying the portions and the buildings of an urban area most susceptible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…It has been demonstrated that this strategy works well for comprehending and handling the complexity of urban surroundings, especially in cities like Fortaleza which are expanding quickly. Another example of a case study using 3D GIS in urban landscapes is research that was conducted on the island [72]. In their research, Morosini and Zucaro (2019) aimed to evaluate the usage of land and urban sustainability through GIS technologies.…”
Section: Urban Planning and Developmentmentioning
confidence: 99%
“…It has been demonstrated that this strategy works well for comprehending and handling the complexity of urban surroundings, especially in cities like Fortaleza which are expanding quickly. Another example of a case study using 3D GIS in urban landscapes is research that was conducted on the island [72]. In their research, Morosini and Zucaro (2019) aimed to evaluate the usage of land and urban sustainability through GIS technologies.…”
Section: Urban Planning and Developmentmentioning
confidence: 99%
“…Ahmed (2017) points in particular to the increased efficiency the use of 3D models affords spatial planners: certain buildings that critically exceed the regulatory framework could be identified more quickly. 3D models could even support a more immediate analysis of the results and the impacts of transformations on urban environments (Morosini and Zucaro, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%